Atomically flat single terminated oxide substrate surfaces. Issue 2 (May 2017) - Biswas, Abhijit; Yang, Chan-Ho; Ramesh, Ramamoorthy; Jeong, Yoon H.
Abstract: Scientific interest in atomically controlled layer-by-layer fabrication of transition metal oxide thin films and heterostructures has increased intensely in recent decades for basic physics reasons as well as for technological applications. This trend has to do, in part, with the coming post-Moore era, and functional oxide electronics could be regarded as a viable alternative for the current semiconductor electronics. Furthermore, the interface of transition metal oxides is exposing many new emergent phenomena and is increasingly becoming a playground for testing new ideas in condensed matter physics. To achieve high quality epitaxial thin films and heterostructures of transition metal oxides with atomically controlled interfaces, one critical requirement is the use of atomically flat single terminated oxide substrates since the atomic arrangements and the reaction chemistry of the topmost surface layer of substrates determine the growth and consequent properties of the overlying films. Achieving the atomically flat and chemically single terminated surface state of commercially available substrates, however, requires judicious efforts because the surface of as-received substrates is of chemically mixed nature and also often polar. In this review, we summarize the surface treatment procedures to accomplish atomically flat surfaces with single terminating layer for various metal oxide substrates. We particularly focus on the substrates with lattice constant ranging from 4.00 Å to 3.70 Å, as the lattice constant of most perovskite materials falls into this range. For materials outside the range, one can utilize the substrates to induce compressive or tensile strain on the films and explore new states not available in bulk. The substrates covered in this review, which have been chosen with commercial availability and, most importantly, experimental practicality as a criterion, are KTaO3, RE ScO3 ( RE = Rare-earth elements), SrTiO3, La0.18 Sr0.82 Al0.59 Ta0.41 O3 (LSAT), NdGaO3, LaAlO3, SrLaAlO4, and YAlO3 . Analyzing all the established procedures, we conclude that atomically flat surfaces with selective A- or B-site single termination would be obtained for most commercially available oxide substrates. We further note that this topmost surface layer selectivity would provide an additional degree of freedom in searching for unforeseen emergent phenomena and functional applications in epitaxial oxide thin films and heterostructures with atomically controlled interfaces.